The Spotify Effect: Peranan Spotify for Artists dalam Industri Musik 4.0 - Fadryona, Riesti (School of Communication - Atma Jaya Catholic University of Indonesia, 2020)
Digitalization of music has been considered to give artists more damage from issues like piracy to artist’ royalties. Spotify claims their platform has the ability “to unlock the potential of human creativity— by giving a million creative artists the opportunity to live off their art”. Spotify has launched the app Spotify for Artists as a tool to let people in the music industry, not just musicians but also songwriter, producer, even manager, to manage their cultural contents in one platform while making revenues. Using the “Spotify Effect” concept from Vonderau (2019) and secondary data analysis, this research wants to explain the feature in Spotify for Artists that can be used to support musicians in industry 4.0. This study found that Spotify is a form of asynchronous CMC with features like direct upload, new release promotions, playlists, merchandising, tours, and statistics, that allow for interactivities between musicians and audiences.